Price Theory and Oligopoly - Bloch, Harry; Bhattacharya, M. (Oesterreichische Nationalbank, 2014)
In his seminal article, ‘Price theory and oligopoly’ (Rothschild 1947), Kurt Rothschild critically reviews recent developments in the theory of imperfect competition and puts forward several ideas on how the theory might develop in the future. Subsequent developments in the theory of imperfect competition have shown the fruitfulness of his ideas. In this paper we review these developments and discuss the correspondence to Rothschild’s original propositions. We also discuss ideas from Rothschild (1947) and his later writings that can stimulate developments in price theory in the future.